Impact of TCAM size on power efficiency in a network of OpenFlow switches. Issue 6 (3rd November 2020) - Ghiasian, Ali
Abstract : Recent developments in networking include the interest in software‐defined networking, in which OpenFlow switches are in charge of forwarding traffic by matching incoming packets with forwarding rules in their flow tables. Flow tables are commonly implemented in ternary content addressable memories (TCAMs). Typically, this type of memory tends to be extremely expensive and to be power‐hungry devices. The price and power dissipation of TCAM depend on the capacity of the memory. A blind design of memory size can result in dramatic degradation in performance and power efficiency of the entire network. In this study, the authors clarify this impact and show how the optimum value of TCAM capacity is attainable. They also propose a power consumption model for TCAM‐based OpenFlow switches. Simulation results show that the proposed solution reduces the average power consumption by 24% compared to the minimum link on method and by 11.5% compared to the minimum node on (MNO) method and thus power efficiency is better achieved when each memory is supplied by appropriate TCAM size.